Assessment of the clinical usefulness of ultrasound‐guided cytological specimens obtained from gastrointestinal lesions in dogs and cats. (5th January 2021) - Turner, R. B. S.; Liffman, R.; Woodward, A. P.; Beck, C.; Courtman, N.; Dandrieux, J. R. S.
Abstract : Objectives: Cytological biopsies are an integral additional test to an abdominal ultrasound when a lesion is identified, but there is little published on factors that that may impact achieving a clinically useful sample of gastrointestinal lesions obtained by ultrasound‐guided fine‐needle cytologic biopsy. This retrospective, descriptive study aimed to assess factors that may influence the clinical usefulness of submitted cytological samples collected from gastrointestinal lesions by ultrasound‐guided percutaneous fine‐needle cytologic biopsy. Material and Methods: Gastrointestinal cytological samples obtained from 25 dogs and 19 cats over 2.5 years were reviewed and determined as clinically useful or clinically useless as per the cytology report. Variables dependent on the ultrasound exam that were used in the analysis included lesion location, lesion thickness, loss of gastrointestinal layering, and the number of slides submitted. Results: Thirty (30/44) of the submitted cytological samples were considered clinically useful. Factors associated with achieving a clinically useful sample in univariable models included the number of slides submitted and the thickness of the lesion. However, these two variables appear inter‐related, as a weak correlation existed between them. Where histologic biopsies were obtained, a clinically useful sample had a partial or complete agreement with histology in three of 12 and eight of 12 cases, respectively. Clinical Significance: Ultrasound‐guided fine‐needle cytological biopsies of gastrointestinal masses provided a clinically useful sample in two‐third of the cases, especially if more slides were provided to the cytologist and thicker lesions were sampled.